Metadata in practice - Hillmann, Diane I. (American Library Association, 2004)
Traditional librarians are often intimidated by the new world of metadata, most especially those without a specialized background in cataloging. Colleagues in general and special libraries who have become adept with it explain some of the more widely used methods for project-based implementations, and ponder the future of metadata development and practice.